Dramatic Jouissance in Edward Bond’s Born - Kate KATAFIASZ (E-REA)
Edward Bond’s 2006 play Born is set in a police state, and is haunted by recurrent rattling sounds. The article suggests that these disturbances to audio visual synchrony may be used to stage Lacan’s ‘fluid’ relationship between signifier and signified, allowing audiences to encounter “radical points in the real” characterised by souffrance – a painful suspense, where reality is “awaiting attention” (Seminar XI 55, 56). Here, the relationship between perception and consciousness may be stretched, ruptured, and reversed, to produce extraordinarily different states of awareness. The article investigates how they are reversed in Bond’s police state, inverting symbolic relationships so that the signifier does not represent physicality as we might suppose; instead physicality unwittingly endorses the signifier, which entraps and commands it in various ways. The article argues that comedy and tragedy are fundamentally democratic tropes because they correct this authoritarian inversion; comic jouissance emerging when physicality subverts the signifier; tragic jouissance disrupting the entire symbolic order with its uncompromising prioritisation of corporeality.